Unlocking Performance: Analysis of Quality Management Practices and Administrative Innovation in Private Universities - Velanska Dixie Namira; Timotius Febry Christian (Pusat Penerbitan dan Publikasi Ilmiah, FEB, Universitas Muslim Indonesia, 2024)
The successful implementation of TQM in the manufacturing industry has led many other industries to start trying to implement TQM. In this study, researchers want to know whether the application of TQM can have a significant effect if applied in the education industry. This study used a quantitative approach to test a predetermined model. This study uses quantitative analysis approach Partial Least Square structural equation model (PLS-SEM). Researchers use Smart-PLS 4.0 software in data processing. The results of data processing and analysis show that there are 2 accepted hypotheses, namely soft TQM has a positive influence on administrative innovation, and administrative innovation has a positive influence on organizational performance. In this study, hard TQM has no effect on administrative innovation and organizational performance.